The International Encyclopedia of Ethics 2013
DOI: 10.1002/9781444367072.wbiee338
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Restoration

Abstract: Ecological restoration is the practice of ecosystem management that alters an ecosystem, site, or area in order to return it to an earlier state. Restoration is most commonly intended to reestablish conditions at a site prior to a specific human intervention, especially resource extraction, by changing a degraded system's structure, function, diversity, and/or processes so that the system appears less disturbed and is self‐sustaining. Elements of an ecosystem usually managed during restoration include surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 3 publications
3
30
0
Order By: Relevance
“…The identification of clumpy galaxies in the dominant population of irregular galaxies at high redshift dates back to the first deep Hubble Space Telescope (HST) images (e.g., Williams et al 1996). Subsequent studies at z ∼ 1 − 3 revealed that clumpy galaxies are more numerous than in the local Universe (e.g., Abraham et al 1996;van den Bergh et al 1996;Giavalisco et al 1996;Elmegreen et al 2004;Elmegreen & Elmegreen 2006;Elmegreen et al 2007Elmegreen et al , 2008Elmegreen et al , 2009Elmegreen et al , 2013Kubo et al 2013Kubo et al , 2016Glazebrook 2013;Tadaki et al 2014;Murata et al 2014;Guo et al 2015;Garland et al 2015;Bournaud 2016). The fraction of clumpy galaxies was studied from z=0 up to the most distant galaxies identified today at z∼10 (Ravindranath et al 2006;Guo et al 2012Guo et al , 2015Shibuya et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The identification of clumpy galaxies in the dominant population of irregular galaxies at high redshift dates back to the first deep Hubble Space Telescope (HST) images (e.g., Williams et al 1996). Subsequent studies at z ∼ 1 − 3 revealed that clumpy galaxies are more numerous than in the local Universe (e.g., Abraham et al 1996;van den Bergh et al 1996;Giavalisco et al 1996;Elmegreen et al 2004;Elmegreen & Elmegreen 2006;Elmegreen et al 2007Elmegreen et al , 2008Elmegreen et al , 2009Elmegreen et al , 2013Kubo et al 2013Kubo et al , 2016Glazebrook 2013;Tadaki et al 2014;Murata et al 2014;Guo et al 2015;Garland et al 2015;Bournaud 2016). The fraction of clumpy galaxies was studied from z=0 up to the most distant galaxies identified today at z∼10 (Ravindranath et al 2006;Guo et al 2012Guo et al , 2015Shibuya et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Locally, we can use present-day stellar kinematics to infer the past evolution of our Milky Way (MW) through Galactic Archeology, (e.g., Belokurov et al 2018;Frankel et al 2018Frankel et al , 2019. At higher redshift, large galaxy surveys are yielding results on the evolution of populations of galaxies over time (e.g., see the review by Glazebrook 2013). If the MW (and other local galaxies) kinematically evolve in a fashion similar to high z galaxies, then in principle results from these two epochs should be able to be explained within the same theoretical framework.…”
Section: Introductionmentioning
confidence: 99%
“…When combined with the Schmidt-Kennicutt star formation relation, the gas surface density is also tied to the star formation rate, (e.g., Green et al 2014;Leroy et al 2016;Semenov et al 2016). If the disk is marginally stable, and it is assumed that gas (rather than stars) is the predominant component of the gravitational potential, the higher gas surface densities and gas fractions at higher redshift (e.g., Genzel et al 2006;Daddi et al 2010;Jones et al 2010;Genzel et al 2011;Tacconi et al 2013;Glazebrook 2013;Popping et al 2015;Krumholz & Burkhart 2016;Stott et al 2016;Wiklind et al 2019) should naturally lead to higher gas velocity dispersion. For more local galaxies, feedback from star-formation may also play a critical role in setting a dynamical "floor" for the star-forming gas (e.g., Agertz et al 2009;Faucher-Giguère et al 2013;Stilp et al 2013;Semenov et al 2018;Orr et al 2019a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The kinematic characterization of different galaxy populations is a key observational input in distinguishing between different evolutionary paradigms, such as the "major merger" (Tacconi et al 2006(Tacconi et al , 2008Kartaltepe et al 2012) and the "steady cold gas accretion" (Kereš et al 2005;Ocvirk et al 2008;Dekel et al 2009a;Ceverino et al 2010) scenarios, since it allows one to determine the fraction of rotating disks to mergers at different cosmic epochs (see e.g., Genzel et al 2001;Tacconi et al 2008;Dekel et al 2009b;Förster Schreiber et al 2009;Bournaud et al 2011;Epinat 2011;Glazebrook 2013;Bellocchi et al 2016). Kinematics is also important in the study of physical processes that govern the formation and evolution of the galaxies, providing a powerful diagnostic to infer the main source of dynamic support (Puech et al 2007;Epinat et al 2009;Cappellari et al 2013;Zhu et al 2018), to distinguish between relaxed virialized systems and merger events (Flores et al 2006;Shapiro et al 2008;Bellocchi et al 2012Bellocchi et al , 2016Barrera-Ballesteros et al 2015), to infer fundamental galaxy quantities like the dynamical mass (Colina et al 2005;Bellocchi et al 2013;Aquino-Ortíz et al 2018), and also to detect and characterize radial motions associated with feedback mechanisms, like massive gas outflows (Shapiro et al 2009;Rupke & Veilleux 2013;López-Cobá et al 2017a,b;Maiolino et al 2017).…”
Section: Introductionmentioning
confidence: 99%